PENGARUH MEMBATIK TERHADAP KEMAMPUANMOTORIK HALUS ANAK DI TK PERTIWI GESIKHARJO - Efendi, Dwi Imam; Jaya, allan Firman (GCEJ (Golden Childhood Education Journal), 2024)
The purpose of this study is to ascertain how batik affects the young children at Pertiwi Gesikharjo Kindergarten's fine motor abilities. Drawing and coloring exercises are frequently encountered in the field as fine motor development activities. Thus, the researcher hopes to assess how Pertiwi Gesikharjo Kindergarten students' fine motor skills are developing with the use of this batik. A quasi experiment is the quantitative research technique that was applied. The population consists of 45 TK Pertiwi Gesikharjo students from groups B1, B2, and B3. With 15 members each, Group B1 served as the experimental sample and Group B2 as the control sample. Cluster Sampling was the method of sampling that was employed. Also, the method of gathering data made use of teacher- designed exams